MODERN TRENDS IN TOURISM DEVELOPMENT IN JORDAN (Web of Teachers: Inderscience Research, 2025)
The article examines the dynamics of tourism industry development in the Hashemite Kingdom of Jordan, analyzing key trends and factors influencing its growth. The role of government measures to stimulate the industry is emphasized, including infrastructure development and promotion of the national tourism product at the international level. Analysis of statistical data from the Central Bank of Jordan allows us to conclude that there is a gradual stabilization of the sector and positive prospects despite persistent external risks.